A companion to American literature - Belasco, Susan 1950-; Gaul, Theresa Strouth; Johnson, Linck; Soto, Michael (Wiley-Blackwell, 2020)
"The test of time," an abundant literature, geographical expansiveness, artistry, and, more recently, inclusiveness represented by a complex awareness of gender and cultural diversity. These are key criteria used to determine entry into American literary canons and American literary histories. Scholars who specialize in indigenous oral literatures would doubtless claim that this literature fulfills all the criteria and thus deserves a major place in canon and history. For these readers, I could proceed directly to the main business of this chapter: an overview of how Native oral narratives, song, and ceremony have and will continue to challenge in constructive ways EuroAmerican concepts of authorship, context, genre, geographic and period designation, the functions of literature, and the importance of understanding how literature is experienced. But most American literature teachers and students have little knowledge of the magnitude and importance of the oral literatures. For these readers, it is appropriate to begin by establishing how this form of literature fulfills conventional expectations for inclusion in a twenty-first century literary history-and specifically inclusion as the grand opening entry to the narrative of our literature"--